Quantum Simulations of Charge Separation at a Model Donor-Acceptor Interface: Role of Delocalization and Local Packing - Allen Kelley; Kush Patel; Eric R. Bittner (Advances in Condensed Matter Physics)
Organic Polymer-based photovoltaic systems offer a viable alternative to more standard solid-state devices for light-harvesting applications. In this study, we investigate the electronic dynamics of a model organic photovoltaic (OPV) heterojunction consisting of polyphenylene vinylene (PPV) oligomers and a [6,6]-phenyl C61-butyric acid methyl ester (PCBM) blend. Our approach treats the classical molecular dynamics of the atoms within an Ehrenfest mean-field treatment of the π-π⁎ singly excited states spanning a subset of donor and acceptor molecules near the phase boundary of the blend. Our results indicate that interfacial electronic states are modulated by C=C bond stretching motions and that such motions induce avoided crossings between nearby excited states thereby facilitating transitions from localized excitonic configurations to delocalized charge-separated configurations on an ultrafast time-scale. The lowest few excited states of the model interface rapidly mix allowing low frequency C-C out-of-plane torsions to modulate the potential energy surface such that the system can sample both intermolecular charge-transfer and charge-separated electronic configurations on sub-100 fs time scales. Our simulations support an emerging picture of carrier generation in OPV systems in which interfacial electronic states can rapidly decay into charge-separated and current producing states via coupling to vibronic degrees of freedom.